2014
DOI: 10.1007/s10961-014-9364-9
|View full text |Cite
|
Sign up to set email alerts
|

Geographic proximity and university–industry interaction: the case of Mexico

Abstract: This paper analyses whether geographic proximity favours specific channels of university-industry interaction when firms collaborate with universities and with government research centres. Our study also provides insights regarding the relationship between the associated channel and the role of firms' absorptive capacities. Our results show that firms with higher levels of absorptive capacities tend to interact more independently of their location. Additionally, interaction with non-local universities generall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 68 publications
0
37
0
8
Order By: Relevance
“…By contrast, recent studies show that firms often search for high-quality, geographically distant universities that can solve their innovation problems (D'Este & Iammarino, 2010;De Fuentes & Dutrénit, 2014;Laursen et al, 2011;Muscio, 2013). Thus, although geographical proximity is one factor that determines whether a firm will collaborate with academic partners in order to benefit from enhanced interactive learning through co-location, other factors may influence a firm's decision to collaborate with a certain university since the firm may require a broad set of academic capabilities to help solve its innovation problems (Bishop, D'Este, & Neely, 2011;D'Este et al, 2013).…”
Section: Main Conceptual Remarks Geographical Distance and Universitymentioning
confidence: 95%
See 3 more Smart Citations
“…By contrast, recent studies show that firms often search for high-quality, geographically distant universities that can solve their innovation problems (D'Este & Iammarino, 2010;De Fuentes & Dutrénit, 2014;Laursen et al, 2011;Muscio, 2013). Thus, although geographical proximity is one factor that determines whether a firm will collaborate with academic partners in order to benefit from enhanced interactive learning through co-location, other factors may influence a firm's decision to collaborate with a certain university since the firm may require a broad set of academic capabilities to help solve its innovation problems (Bishop, D'Este, & Neely, 2011;D'Este et al, 2013).…”
Section: Main Conceptual Remarks Geographical Distance and Universitymentioning
confidence: 95%
“…In general, these studies have found empirical evidence of the presence of geographically bounded spillovers from academic research to industrial innovation (Anselin, Varga, & Acs, 1997;Arundel & Geuna, 2004;Audretsch & Feldman, 1996;D'Este & Iammarino, 2010;De Fuentes & Dutrénit, 2014;Jaffe, 1989;Laursen et al, 2011;Mansfield & Lee, 1996).…”
Section: Main Conceptual Remarks Geographical Distance and Universitymentioning
confidence: 99%
See 2 more Smart Citations
“…Tal interação pode acontecer através de variados canais, formais ou informais. Os canais mais reconhecidos na literatura são: contratos conjuntos de P&D; mobilidade de recursos humanos (estudantes e acadêmicos); redes; difusão de informação através de publicações, conferências e internet; consultoria e treinamento; direito de propriedade; incubadoras e spin-offs (DE FUENTES;DUTRENIT, 2012).…”
Section: Relação Entre "Serviços" Demandados Pelas Empresas Na Interaunclassified